I - Tarshis, L. (Review of Economic Studies, 1934)
Journal Article Notes on the Elasticity of Substitution: I Get access L. Tarshis L. Tarshis Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 144–147, https://doi.org/10.2307/2967621 Published: 01 February 1934